1995
DOI: 10.1029/94jc01448
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability in the vertical structure of bioluminescence in the North Atlantic Ocean

Abstract: The temporal and depth variability of stimulated bioluminescence at 59øN, 21øW in the North Atlantic during 1991 was measured by two bathyphotometers (BP's). A moored BP (MOORDEX) obtained a 106-day time series of bioluminescence at 50 m between May 1 and August 15. A profiling BP (high-intake, defined excitation, HIDEX) measured bioluminescence in the upper water column during cruises in May and August. MOORDEX-measured bioluminescence intensity cycled with an approximate 20-day periodicity. In May, biolumine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…This strengthens the inference that the physical environment in the bight is fairly stable with respect to seasonality, and that bioluminescence is strongly influenced by seasonal rainfall and runoff. Southern California Bight bioluminescence is similar to that found in coastal waters of Vestfjord, Norway (Lapota 1990, unpublished), and the Arabian Sea (Lapota & Rosenberger 1990), but higher than that found in the Sargasso Sea (Batchelder & Swift 1989), the North Atlantic (Neilson et al 1995) and the Beaufort Sea (Lapota et al 1992). The vertical structure of bioluminescence was correlated with Chl fluorescence for some of the stations in the Bight.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This strengthens the inference that the physical environment in the bight is fairly stable with respect to seasonality, and that bioluminescence is strongly influenced by seasonal rainfall and runoff. Southern California Bight bioluminescence is similar to that found in coastal waters of Vestfjord, Norway (Lapota 1990, unpublished), and the Arabian Sea (Lapota & Rosenberger 1990), but higher than that found in the Sargasso Sea (Batchelder & Swift 1989), the North Atlantic (Neilson et al 1995) and the Beaufort Sea (Lapota et al 1992). The vertical structure of bioluminescence was correlated with Chl fluorescence for some of the stations in the Bight.…”
Section: Discussionmentioning
confidence: 57%
“…While many oceanographic studies have focused on the distribution of bioluminescence in the marine environment (Stukalin 1934, Tarasov 1956, Seliger et al 1961, Clarke and Kelly 1965, Bityukov 1967, Lapota and Losee 1984, Swift et al 1985, Lapota et al 1988, Batchelder and Swift 1989, Lapota et al 1989, Lapota and Rosenberger 1990, Neilson et al 1995, Ondercin et al 1995, Swift et al 1995, little understanding of the seasonality and sources of planktonic bioluminescence in coastal waters and open ocean has emerged. Some previous studies with respect to annual cycles of bioluminescence were severely limited in duration as well as in the methods used to quantify bioluminescence (Bityukov 1967, Tett 1971.…”
Section: Introductionmentioning
confidence: 99%
“…While many oceanographic studies have focused on the distribution of bioluminescence in the marine environment (Stukalin 1934, Tarasov 1956, Seliger et al 1961, Clarke and Kelly 1965, Bityukov 1967, Lapota and Losee 1984, Swift et al 1985, Lapota et al 1988, Batchelder and Swift 1989, Lapota et al 1989, Lapota and Rosenberger 1990, Neilson et al 1995, Ondercin et al 1995, Swift et al 1995, little understanding of the seasonality and sources of planktonic bioluminescence in coastal waters and open ocean has emerged. Some previous studies with respect to annual cycles of bioluminescence were severely limited in duration as well as in the methods used to quantify bioluminescence (Bityukov 1967, Tett 1971.…”
Section: Introductionmentioning
confidence: 99%
“…Bathyphotometers have provided information about bioluminescent organisms, specifically the spatial and temporal location of BL as well as its relationship with other measured biological, physical, and chemical parameters in the ocean (e.g., Neilson et al 1995;Widder et al 1999;McManus et al 2003). Using a BP, Swift et al (1983) and Batchelder and Swift (1989) showed that zooplankton were usually major sources of epipelagic BL in the southern Sargasso Sea, except when the concentration of the BL dinoflagellate Pyrocystis noctiluca was high.…”
mentioning
confidence: 99%
“…Bathyphotometers with high flow rates (18 L s -1 and higher), such as HIDEX (Widder et al 1993;Neilson et al 1995), were initially designed to ensure optimal capture efficiency in the open ocean where bioluminescent organisms vary widely in abundance and ability to avoid capture. In coastal waters, such high flow rates and large instruments might obscure the fine-scale distribution of bioluminescent organisms, and make it difficult to discriminate individual organisms amidst the bulk BL signal.…”
mentioning
confidence: 99%